VALUATION TECHNIQUES USED IN FAIR VALUE MEASUREMENT - Cristina-Aurora, BUNEA-BONTAS (Strategii Manageriale, 2013)
Valuation of assets and liabilities involves significant judgements and estimates, especially when fair value measurement is required. Currently, IFRS 13 Fair Value Measurement offers a single and more comprehensive source of guidance that is applied to almost all fair value estimates. When measuring fair value of fixed assets, intangible assets, specified financial assets or liabilities, different valuation techniques may be used: the market approach, the cost approach and the income approach. This article reviews these techniques and points out that different valuation practices may provide different results depending on the item being fair valued and on the inputs used. Also it emphasizes that, in particular circumstances, there is the possibility that a certain technique may be more appropriate than other.